(untitled) (Research, Society and Development, 2019)
This article aims to carry out a survey of publications that refer to the study of the impacts of the oil spill on sea fishing, in order to search for existing works and present a portfolio for future research. For the research the Web of Science database was used where a qualitative analysis is carried out regarding the selected articles. In addition to the qualitative analysis, a bibliometric analysis of citation and cocitation was carried out using the CiteSpace software and a network of collaborations between authors was verified using Google Earth. Among the 14 selected journals, the most prominent journal in this area is PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE UNITED STATES OF AMERICA. It is noted that the USA, Canada and Europe have current research partnerships. The results show that the publications are converging to two areas, one in the environmental area and another in the economic area, but research focused on the economic impact is timid, showing an area that needs further research.